The Effect of Composting Azolla Compost Fertilizer and Humic Material on CO2 Gas Production in Sand Land - Febrianti Rosalina; Muhammad Syahrul Kahar (Bioscience, 2018)
his study was an experimental study which aimed to determine the effect of Compost Azolla Fertilizer (KA) and the addition of humic material (H) on the sand soil to the levels of CO2 produced in the respiration process of soil microorganisms (incubation soil conditions). The design used is a Completely Randomized Design (CRD) consisting of 9 treatments, namely 300 kg ha-1 urea (U), 4 tons ha-1 KA (T1), 15 liters ha-1 H (T2), 2 tons ha-1 KA + 15 liters ha-1 H (T3), 4 tons ha-1 KA + 15 liters ha-1 H (T4), 6 tons ha-1 KA + 15 liters ha-1 H (T5), 2 tons ha-1 KA + 30 liters ha-1 H (T6), 4 tons ha-1 KA + 30 liters ha-1 H (T7), 6 tons ha-1 KA + 30 liters ha-1 H (T8) and 1 control (K ) without the addition of train and H with 3 replications. Measurement of carbon dioxide (CO2) levels from each sample using gas chromatography equipped with TCD (Thermal Conductivity Detector). The statistical data analysis used was the F test, whereas to see the difference in the effect of each treatment, the BNT test was used. The results showed that Azolla compost fertilizer and humic material on sand soil had an effect on the level of CO2 gas production produced in the soil microorganisms respiration process, where the concentration of Azolla compost fertilizer and humic material which most affected the increase of CO2 gas production in sand soil was treated with the highest concentration of 6 tons ha-1 Azolla + 30 liter compost fertilizer ha-1 H (T8).